Violence and Truth in 2022’s Epoch End: COVID-19 and Russia’s Invasion of Ukraine in the World Historical Context - Kennedy, Michael D. (Journal of Public Governance, 2022)
Objective: In this research article, I seek to explain the cultural logics and practices of narratives of global transformations and thereby demonstrate the significance of articulation and rearticulation in their constitution. I focus on cultural politics from within narratives – through the fall of 2022 – organising our sense of the COVID-19 pandemic on the one hand, and Russia’s invasion of Ukraine on the other. Research Design & Methods: This is a theoretical paper, with references to numerous Web articles, newspapaer articles, and some research volumes. Findings: I conclude by reflecting on the ways in which these narratives can be rearticulated in order to develop a more global solidarity in the epoch end’s policy and practice. Implications/Recommendations: This paper is relevant to the research into further interactions between wars and epidemics, as well as for researching the consequences of the Russian invasion into Ukraine. Contribution/Value Added: This paper is original in presenting an insight into the connection between the COVID-19 pandemic and the violence taking place in Ukraine as of February 24th, 2022.